The Impacts of Illegal Toxic Waste Dumping on Children’s Health: A Review and Case Study from Pasir Gudang, Malaysia - Ibrahim, Mohd Faiz (Int J Environ Res Public Health, 2021)
Poor management of hazardous waste can lead to environmental pollution, injuries, and adverse health risks. Children’s exposure to hazardous waste may cause serious acute and chronic health problems due to their higher vulnerability to the toxic effects of chemicals. This study examines an incident of illegal chemical dumping in Pasir Gudang, Malaysia and its potential health impacts on children. The study introduced a risk assessment of possible health-related effects due to chemical contamination based on a real case scenario where quantification of the contamination was not feasible. A literature review and spatial analysis were used as research methods. On 6th March 2019, tons of hazardous waste were illegally disposed into Kim Kim River, Pasir Gudang, Malaysia. They were identified as benzene, acrolein, acrylonitrile, hydrogen chloride, methane, toluene, xylene, ethylbenzene, and d-limonene. As a result, 975 students in the vicinity developed signs and symptoms of respiratory disease due to the chemical poisoning. The findings of this study indicate that more effective policies and preventive actions are urgently needed to protect human health, especially children from improper hazardous waste management.